THE EFFECT OF MARKETING MIX 7P ON DECISIONS PURCHASE AND CONSUMER LOYALTY OF UNITS CENTRAL APARTMENT EAST RESIDENCE - Vitto Rialialie; Jerry Heikal (Sean Institute, 2023)
This study aims to determine product, price, promotion, place, people, process, And Physical Evidence influential in a manner simultaneous nor Partial to decision purchase And loyalty consumer. Population in study This is consumer Apartment Center East Residence. Sample Which used in study This is consumer as many as 192 people with accidental sampling technique. Which is used for this research is validity And reliability For testing instrument Which applied, method quantitative with Smart PLS data processing. The result is price, people, process, product and promotion No influential in decision purchase. Whereas physical evidence And place influential in purchasing decisions. Then people, physical evidence, and place are not effect on consumer loyalty. While price, process, product d an promotion influential on consumer loyalty.